The Impact of the Coronacrisis on KIBS Sector - Miles, Ian; Belousova, Veronika; Chichkanov, Nikolay; Krayushkina, Zhaklin (Foresight and STI Governance, 2021)
Knowledge-Intensive Business Services (KIBS) are problem-solvers for other organizations. The coronacrisis affects KIBS directly, but also means that their clients are confronting new problems. How are KIBS addressing these two sets of challenges? This paper draws on material available in the trade and industry press, on official reports and statistics, and the early academic studies addressing these themes. We find that KIBS have been active (alongside other organizations) in providing a substantial range of services aimed at helping their clients (and others) deal with various contingencies thrown up by the crisis. Not least among these is the need to conform to shifting regulatory frameworks, and requirements for longer-term resilience. KIBS themselves have had to adapt their working practices considerably, to reduce face-to-face interaction with clients and within teams collaborating on projects. Adaptation is easier for those whose tasks that are relatively standardized and codified, and it remains to be seen how far a shift to such activities - and away from the traditional office-based venues of activity - is retained as firms recover from the crisis. KIBS are liable to play an important role in this recovery from the crisis, and policymakers can mobilize their services. Some KIBS are liable to be critical for rendering economies more resilient in the face of future pandemics and we argue that these firms are also important for confronting the mounting climate crisis.